Structural behavior of RC beam-column subassemblages under a middle column removal scenario - Yu, Jun (2013)
Six RC beam-column subassemblages, consisting of two single-bay beams, one middle joint, and two end column stubs, were quasi-statically tested under a middle column removal scenario. The tests were aimed at investigating whether there are alternate load paths that can mitigate progressive collapse. With adequate axial restraints, both compressive arch action (CAA) and catenary action could be mobilized, significantly increasing the structural resistance beyond the beam flexural capacity. The effects of the top and bottom reinforcement ratios at the joint interfaces and beam span-to-depth ratio on structural behavior were studied. The results show that CAA is more beneficial to subassemblages with a short span-to-depth ratio and a low reinforcement ratio, whereas catenary action is more favorable to subassemblages with a large span-to-depth ratio and a high reinforcement ratio, particularly the top reinforcement ratio. As the last defense mechanism to prevent structural collapse, the development of catenary action is highlighted. The onset of catenary action corresponds to the transition of beamaxial force from compression to tension, typically occurring at a central deflection around one beam depth in the tests if no shear failure precedes catenary action.At the catenary action stage, prior to fracture of the bottom bars, structural resistance is contributed by both beam axial tension from longitudinal reinforcement and shear force because of dowel action. If the contribution from rising axial tension exceeds the loss as a result of declining shear force, the structural resistance will still keep on increasing until the fracture of the top bars. Finally, the authors suggest a deformation criterion to determine the catenary action of RC subassemblages; i.e., when the deflection at the middle joint attains 10% of the total beam span length, catenary action capacity is reached. The conservatism of this criterion for design purposes is also discussed.